X.500 and LDAP security a comparative overview. - Hassler, V. (IEEE Network : the magazine of global information exchange)
We give a comparative overview of the X.500 and LDAPv3 Directory security features. X.500 is a commonly used name for a series of joint ISO/IEC and ITU-T standards specifying a distributed directory service. It assumes the existence of an underlying OSI protocol stack. LDAP is an Internet alternative to the X.500 Directory Access Protocol (X.511 DAP). Since its first version LDAP has undergone significant changes, and many of them concern security. It was originally planned to use LDAP only to access the X.500 directory via an LDAP gateway. In the meantime, LDAP functionality was extended, which enables LDAPv3 to be used for both the server model and the client read and update access protocol